ESTRATEGIAS DE GAMIFICACIÓN Y SU INFLUENCIA EN EL RENDIMIENTO ACADÉMICO DE LOS ESTUDIANTES DEL 5TO AÑO DE LA ESCUELA DE EDUCACIÓN BÁSICA “CIUDAD DE BABAHOYO” Y LA UNIDAD EDUCATIVA “JUAN E. VERDESOTO” DE LA PQA. CLEMENTE BAQUERIZO DE LA CIUDAD DE BABAHOYO 2024-2025 - MERA SOLEDISPA NICOLE DAYANNA (2024)
Gamification is a strategy that consists of the application of elements in the game mechanics in the playful context, this focuses on addressing the need to find effective methods that are effective in improving academic performance. The study aimed to identify the influence of gamification strategies on the academic performance of students in the 5th year of EGB in Basic Education Schools in the Clemente Baquerizo parish of the city of Babahoyo. The application of gamification strategies was useful to change the traditional teaching method. In addition, tools such as surveys and observation were used, which allowed us to know how academic performance is changing, when implementing gamified classes in the educational institution. The study had a mixed approach because it combined both the qualitative and quantitative methods, which facilitated the collection, analysis and integration of data that provided us with a better understanding of how the variables are related within the established context. The purpose of gamification not only favored academic learning, but also enhanced socio-emotional skills such as teamwork and emotional management.